2021
DOI: 10.3389/fgene.2021.651610
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Signatures and Rules of Circulating Extracellular MicroRNA for Distinguishing Cancer Subtypes

Abstract: Cancer is one of the most threatening diseases to humans. It can invade multiple significant organs, including lung, liver, stomach, pancreas, and even brain. The identification of cancer biomarkers is one of the most significant components of cancer studies as the foundation of clinical cancer diagnosis and related drug development. During the large-scale screening for cancer prevention and early diagnosis, obtaining cancer-related tissues is impossible. Thus, the identification of cancer-associated circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 77 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Chung et al (15) reported let-7b, miR-26a, miR-132, and miR-145 as potential biomarkers in ovarian cancer patients. Among the results of Yuan et al's (16) study, has-miR-6784-5p, has-miR-6800-5p, and has-miR-5100 are indicating ovarian-associated cancer signature. Jeon et al (17) reported that the serum and tissue miR-1290 was significantly elevated in patients with epithelial ovarian cancer compared with patients with benign ovarian neoplasm.…”
Section: Related Workmentioning
confidence: 92%
“…Chung et al (15) reported let-7b, miR-26a, miR-132, and miR-145 as potential biomarkers in ovarian cancer patients. Among the results of Yuan et al's (16) study, has-miR-6784-5p, has-miR-6800-5p, and has-miR-5100 are indicating ovarian-associated cancer signature. Jeon et al (17) reported that the serum and tissue miR-1290 was significantly elevated in patients with epithelial ovarian cancer compared with patients with benign ovarian neoplasm.…”
Section: Related Workmentioning
confidence: 92%
“…A review of the literature suggests that the Boruta method is one of the most effective feature selection methods that allows us to automatically filter out unnecessary features (noise) ( 34 ). This variable selection algorithm has been widely used in previous studies and outperforms the other variable selection methods in various fields, namely, power system transient stability assessment ( 35 ), modeling soil moisture ( 36 ), and medical science ( 37 ). As a result of Boruta’s variable selection method, we obtain a more reliable list of effective features, bearing greater predictive value on the response variable, that can be used in conjunction with the Boruta method.…”
Section: Methodsmentioning
confidence: 99%
“…Lead-time bias occurs when a screeningdetected tumor would have been clinically diagnosed later, after metastasis had occurred, or when the tumor was already incurable at the time of screening detection. 99 In both cases, there is no actual improvement in long-term outcomes. Length-time bias refers to the tendency of screening to preferentially detect slower-growing tumors, which may not significantly impact survival rates.…”
Section: Limitations and Challengesmentioning
confidence: 99%